SISTEM PAKAR PADA PERMAINAN UNTUK MENGUKUR TINGKAT INTELLIGENCE QUOTIENT (IQ) MENGGUNAKAN METODE BINET-SIMON BERBASIS ANDROID - E.N. Tamatjita; Mardiana Irawaty; Rio Ramdhani (Institut Teknologi Dirgantara Adisutjipto, 2016)
The development of mobile technologies very rapidly at this time, can be seen in all areas of human life. It triggers the level of usage of mobile equipment itself, this time in the form of a smartphone gadgets familiar to the adults and children. IQ tests that exist today are still many that are manual and less desirable, especially for the children. With combined by mobile technology and packed into a game, is expected to add to the child's interest and can be used as a means of learning. The test results of 30 respondents, the level of user satisfaction based GUI Display, User Friendly and Final Game IQ Method Using Binet-Simon-Based Mobile, obtained a percentage of 71.31% keselurahan assessment. Thus Game IQ can be said Good